The effect of pedagogical competence and work motivation on teacher instructional innovation - Sari, Ice Linsa; Danim, Sudarwan; Kartiwi, Asti Putri (Institut Agama Islam Negeri Kendari, 2026)
This study investigates the influence of pedagogical competence and work motivation on teacher instructional innovation in junior secondary schools. Using a quantitative correlational design, the study involved 115 teachers selected through saturated sampling. Data were collected through validated questionnaires and analyzed using descriptive statistics and multiple regression techniques. The findings reveal that pedagogical competence, work motivation, and instructional innovation are generally categorized as high, although innovation practices remain uneven. Pedagogical competence has a positive and significant effect on instructional innovation, while work motivation also contributes positively with a lower influence. Simultaneously, both variables demonstrate a strong joint effect on instructional innovation. The study concludes that instructional innovation develops through the interaction between teachers’ professional competence and motivational drive. Therefore, integrative professional development programs and supportive school environments are essential to strengthen sustainable instructional innovation and improve the quality of teaching practices in contemporary educational contexts.